Genetic variability and heritability studies in sunflower inbred lines: Genetic variability and heritability studies in sunflower inbred lines - S J GAHUKAR; SANGITA U FATAK (Journal of Oilseeds Research, 2023)
The experiment was conducted at Oilseeds Research Centre, Dr. PDKV, Akola during Kharif 2020-2021, to study the Genetic Variability studies in Sunflower Inbred Lines. The experiment consisted of 24 sunflower inbred lines were evaluated with three checks (DRSF 108, DRSF 113 and Phule Bhaskar) respectively and was laid out in Randomized Block Design. The study illustrated, the existence of wide ranges of variations for most of the characters among the sunflower inbred lines. Analysis of variation indicated that the mean squares of the genotypes were highly significant for all the characters taken under study. The range of variation, as well as genotypic and phenotypic coefficient of variations were high for seed yield/plant, plant height and test weight indicating the scope of improvement through simple selection procedure for obtaining high yield. Broad-sense heritability estimate was maximum for plant height (98.5), while that for seed yield g/plant (97.4) and head diameter (95.6). Hence, higher heritability estimates for these traits indicated that environmental factors did not greatly affect phenotypic variation of these characters.